Telecommunications Externality on Migration : Evidence from Chinese Villages - Lu, Yi; Xie, Huihua; Xu, Lixin Colin (World Bank, Washington, DC, 2015)
This paper uses a unique natural experiment in Chinese villages to investigate whether access to telecommunications-- in particular, landline phones -- increases the likelihood of outmigration. By using regional and time variations in the installation of landline phones, the difference-in-differences estimation shows that access to landline phones increases the ratio of out-migrant workers by 2 percentage points, or about 50 percent of the sample mean in China. The results remain robust to a battery of validity checks. Furthermore, landline phones affect outmigration through two channels: information access to job opportunities and timely contact with left-behind family members. The findings underscore the positive migration externality of expanding telecommunications access in rural areas, especially in places where migration potential is large.